STRATEGY OF DEVELOPING PASIR PUTIH BEACH WATES TASIKHARJO TOWARDS SOCIAL WELFARE OF LOCAL COMMUNITY - Zulfa, Safira; Falaq, Yusuf (Jurnal Al-Ijtimaiyyah, 2025)
This study focuses on formulating a development strategy for the Pasir Putih Wates Beach Tourism Village in Tasikharjo Village, Kaliori District, Rembang Regency, to enhance the social welfare of the local community. The research employs a descriptive qualitative method with data collection techniques, including observation, interviews, and documentation. The findings reveal that Pasir Putih Wates Beach has significant potential in the tourism sector but faces challenges such as limited infrastructure and suboptimal promotion efforts. The proposed strategies involve developing tourism facilities, enhancing the capacity of local human resources, and optimizing digital promotion. The implementation of these strategies is expected to generate new employment opportunities, drive local economic growth, and preserve local culture, thereby improving the welfare of the community.